Trade in wood-based products in the EU27 - wood content and coverage by the current EUTR and the proposed regulation on deforestation-free value chains - Margret Köthke; Holger Weimar (Johann Heinrich von Thünen-Institut, 2022)
This working paper provides a detailed overview of the trade in wood-based or wood-containing products1 in the EU27 in 2020 and distinguishes products already under the scope of the EUTR and the proposed regulation of the European Commission on deforestation-free value chains, from products not in the scope of those two regulations. The study considers overall 769 products (according to the 8-digit product codes of the Combined Nomenclature) from the entire list of goods for international trade statistics, provided that some wood content can be assumed. Of these products, 348 are already in the scope of the EUTR. The remaining 421 products are considered, to assess their relevance in EU27 wood-based products trade. Therefore, trade values and quantities for each product are taken from EUROSTAT foreign trade data bases. To compare the wood content related to each product, trade quantities were converted into trade volumes of cubic meters of roundwood equivalents (RWE m³). The roundwood equivalent indicates how much raw wood is required to produce the respective wood-based product. Converting the trade volumes into this physical reference value also enables a raw material-related comparison of the traded products. The working paper presents three different trade flows, which all fall within the scope of the proposed new regulation for deforestation-free products: a) Imports of wood-based products from third countries into the EU27, b) exports to third countries from the EU27, and c) intra trade within the EU27 internal market (between EU Member States). Further, detailed information on data compilation, data gaps and uncertainties and conversion factors applied are given within this working paper [...].
urn:nbn:de:gbv:253-202206-dn064958-3
Keywords: 630; European Timber Regulation; EUTR; timber trade; wood-based products; deforestation free value chains